Analysis of Instagram Online Promotion Factors and Electronic Word of Mouth (E-Wom) on Decisions to Visit Cikadongdong River Tubing Tourism - Nurwulan A, Carolin; Seviani, Clarisa; Andika, Ferry; Rahmadi, Rahmadi (Journal of Management Economic and Financial, 2024)
The tourism industry's growth, driven by advances in transportation and IT, has increased the number of destinations, creating intense competition. Managers must offer unique attractions to remain competitive. As a service sector, tourism integrates diverse elements of a destination. Indonesia, with its rich cultural diversity and a projected 2024 population of 279,035,242 (3.45% of the world), attracts many tourists to its exotic islands. This research analyzes the impact of online promotions and electronic word of mouth on the decision to visit the Cikadongdong River Tubing attraction. Using an associative and quantitative approach, the study sampled 100 visitors through purposive non-probability sampling, employing a questionnaire with a Likert scale. Data analysis with SPSS 25 revealed that both online promotion (X1) and electronic word of mouth (X2) significantly and positively influence visit decisions (Y).